ANALYSIS OF DEFECTS IN U-DITCH CONCRETE USING DMAIC METHOD AND RCA METHOD - Risha Siti Aliyah; Inggit Marodiyah (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to analyze the causes of defects and minimize their occurrence in PT XYZ, a concrete company producing U Ditch concrete, which has a defect standard of 0.1%. The percentage of defects from January to November 2023 exceeded this standard. Method: The methods used in this study are DMAIC (Define, Measure, Analyze, Improve, Control) and RCA (Root Cause Analysis). DMAIC is employed to define the level of defect control, while RCA is applied to analyze the root causes of the defects. Result: The results indicate that the highest causes of defects are related to the worker factor, which includes frequent human errors; the material factor, where materials do not meet standards; the machine factor, with inadequate calibration; and the production environment factor, which is still carried out in an open space. The DPMO (Defects Per Million Opportunities) value of PT XYZ is 46,557, meaning there is a possibility of 46,557 defective products per one million products produced. Novelty: The study highlights the importance of a comprehensive analysis using DMAIC and RCA to address the root causes of defects in production processes, which can help the company achieve quality standards and minimize product defects.